1486. Phylogenetic and alpha toxin variant analyses of Staphylococcus aureus strains isolated from patients during the SAATELLITE study. (31st December 2020) - Tabor, David E; Tkaczyk, Christine; Tovchigrechko, Andrey; Sellman, Bret R; McCarthy, Michael; Ren, Pin; Shoemaker, Kathryn; Jafri, Hasan S; François, Bruno; Esser, Mark T; Coppens, Jasmine; Timbermont, Leen; et al.
Abstract: Background: Suvratoxumab is a human monoclonal antibody that neutralizes S. aureus (SA) alpha toxin (AT). SAATELLITE, a phase 2 study of the safety and efficacy of suvratoxumab for reducing the incidence of SA pneumonia (NCT02296320), was conducted within the consortium for Combatting Bacterial Resistance in Europe. Methods: A total of 304 SA isolates (baseline, onset and last available isolates from suspected serious bacterial infections, SSBIs) collected from the lower respiratory tract samples from 165 subjects during SAATELLITE were subjected to whole genome sequencing. AT gene ( hla ) sequences were translated and amino acid variation was identified in comparison to the reference SA USA300 FPR3757. Phylogenetic analysis, genomic annotation and ST analysis were performed. AT expression in SA culture supernatants was performed by ELISA. Representative isolates with novel AT subtypes that had not been identified in previous studies were tested for hemolytic activity and suvratoxumab neutralizing activity. Wilcoxon rank sum test and Fisher's exact test were performed, respectively: a) to compare difference in baseline AT expression in relation to SA pneumonia incidence; b) to evaluate the association between occurrence of AT stop codons and incidence of SA pneumonia at baseline, as well as the association between occurrence of AT stop codons and treatment arms at post baseline. Results: We identified a total of 44 sequence types (STs) and 21 unique AT subtypes, 7 of which have not been described previously. No substitutions were located in the suvratoxumab binding region and all novel AT subtypes displaying lytic activity were neutralized by suvratoxumab. We detected stop codons Q113B and W205B in AT sequences in 53 and 2 SA isolates, respectively. We uncovered no significant associations of: 1) baseline AT expression with SA pneumonia incidence [p=0.967]; 2) occurrence of AT gene stop codon with either SA pneumonia incidence [p >0.999] or suvratoxumab treatment [p=0.103; lower frequency of stop codons in suvratoxumab arm versus placebo]. Conclusion: Our data indicated that: 1) suvratoxumab target region in (AT) remains conserved; 2) suvratoxumab is active against all AT variants identified to date; 3) suvratoxumab did not exert pressure on SA clinical isolates for selection of escape mutants. Disclosures: David E. Tabor, PhD, AstraZeneca (Employee, Shareholder) Andrey Tovchigrechko, PhD, AstraZeneca (Employee, Shareholder)KitePharma, a Gilead company (Employee, Shareholder) Bret R. Sellman, PhD, AstraZeneca (Employee, Shareholder) Michael McCarthy, n/a, AstraZeneca (Employee) Kathryn Shoemaker, MS, AstraZeneca (Employee) Hasan S. Jafri, MD, FAAP, AstraZeneca (Employee) Mark T. Esser, PhD, AstraZeneca (Employee) Alexey Ruzin, PhD, AstraZeneca (Employee, Shareholder)